Adhesives That Contains Ionic Liquids Segment: From Synthesis to Applications - Deng, Qizhe; Xu, Yantao; Chen, Senbin; Zhu, Jintao (Macromolecular rapid communications., 2025)
As technology has developed by leaps and bounds over decades, the development of high‐performance supramolecular adhesives has become crucial in both scientific and industrial fields. Ionic liquids (ILs)‐based adhesives, containing ILs segment, utilizing ILs chemical structure as either the primary adhesive component or key functional group, have materialized as a highly transformative subject matter for cutting‐edge and emerging applications. Rational adhesive design strategies, carefully balancing adhesion and cohesion behavior, are also required when constructing ILs‐based adhesives. Herein, a detailed discussion on the latest advancements is provided in ILs‐based adhesive design, including strategies such as IL monomer decoration/polymerization and the creation of ionogels, etc. Leveraging abundant toolbox of ILs structure and obtained rich (macro)molecular configuration, these adhesives can address both general and specific requirements, offering distinctive advantages and great potential for practical industrial applications. From this perspective, it outlines and summarizes the recent research including rational design and manufacturing technique toward advanced ILs‐based adhesives such as sensory, underwater, electric‐controlled and biomedical applications, particularly proposing the guidance for construction toward tailor‐made glues. Ionic liquids‐based adhesives, as a dynamic bridge between innovative design and diverse applications, present boundless potential alongside challenges. Rising superior to conventional scientific and technological frontiers, these adhesives play a cruial role in sensory, underwater, electric‐controlled and biomedical adhesives. With novel design based on experimental and theoretical contributions, ionic liquids‐based adhesives are poised to achieve remarkable advancements in future.